Characterization and treatment of titanium dioxide, TiO2 via ultrasonic process with melastoma malabathricum as sustainable sensitizer for photovoltaic slar cell - Abdullah, Nur Munirah (2012)
Dye-sensitized solar cells (DSSCs) have been fabricated with doped Titanium Dioxide, TiO2 which are based on natural dyes from Malaysia tropical fruits, wherein contain interlocking groups; the carbonyl and hydroxyl groups of the anthocyanin molecule which enhance the photosensitization effect due to the high interaction on the surface of the film. Such a natural dye extracted from Melastoma Malabathricum can be subjected to molecular tailoring to give a superior dye preparation, offering a wide range of spectral absorption; covering the entire visible region (400 – 700 nm). This study is based on a series of TiO2 preparations designated U1 and U2 (without and with additive respectively), and those treated with ultrasonic energy, namely U3 and U4 (without and with additive respectively). 10 minutes of sonication of the metal oxide led to its breakdown from agglomeration at the micro to the nano scale. Furthermore the additive (4-tert-butylpyridine) in potassium iodide, KI3 electrolyte, effects the rate of electron injection into the oxidized dye sensitizer. Sonication of TiO2 reduced the particle size agglomerates from 0.37 µm down to 0.15 µm; this treatment led to a more consistency with high porosity, enabling enhance absorption and anchorage of the dye sensitizer. Sonicated sample U4, with addition of electrolyte additive gives, open circuit voltage, Voc= 0.742 V, short circuit current, Isc= 0.36 mA, fill factor, FF= 57.012 and 0.039 % of cell’s efficiency. Evidently, sonication and addition of additive for KI3 electrolyte offer enhanced capability for further application.